The transcription factor Spalt and human homologue SALL4 induce cell invasion via the dMyc-JNK pathway in Drosophila. - Sun, J.; Zhang, J.; Wang, D.; Shen, J. (Biology open, 2020)
Cancer cell metastasis is a leading cause of mortality in cancer patients. Therefore, revealing the molecular mechanism of cancer cell invasion is of great significance for the treatment of cancer. In human patients, the hyperactivity of transcription factor Spalt-like 4 (SALL4) is sufficient to induce malignant tumorigenesis and metastasis. Here, we found that when ectopically expressing the Drosophila homologue spalt (sal) or human SALL4 in Drosophila, epithelial cells delaminated basally with penetration of the basal lamina and degradation of the extracellular matrix, which are essential properties of cell invasion. Further assay found that sal/SALL4 promoted cell invasion via dMyc-JNK signaling. Inhibition of the c-Jun N-terminal kinase (JNK) signaling pathway through suppressing matrix metalloprotease 1, or basket can achieve suppression of cell invasion. Moreover, expression of dMyc, a suppressor of JNK signaling, dramatically blocked cell invasion induced by sal/SALL4 in the wing disc. These findings reveal a conserved role of sal/SALL4 in invasive cell movement and link the crucial mediator of tumor invasion, the JNK pathway, to SALL4-mediated cancer progression.This article has an associated First Person interview with the first author of the paper.